Opinions, practice patterns, and perceived barriers to lung cancer screening among attending and resident primary care physicians - Henderson LM; Jones LM; Marsh MW; Brenner AT; Goldstein AO; Benefield TS; Greenwood-Hickman MA; Molina PL; Rivera MP; Reuland DS (Dove Medical Press, 2018)
Louise M Henderson,1 Laura M Jones,1 Mary W Marsh,1 Alison T Brenner,2,3 Adam O Goldstein,4 Thad S Benefield,1 Mikael Anne Greenwood-Hickman,5 Paul L Molina,1 M Patricia Rivera,2 Daniel S Reuland2,3 1Department of Radiology, The University of North Carolina, Chapel Hill, NC, 2Department of Medicine, 3The University of North Carolina Lineberger Comprehensive Cancer Center, 4Department of Family Medicine, The University of North Carolina, Chapel Hill, NC, 5Kaiser Permanente Washington Health Research Institute, Seattle, WA, USA Introduction: The US Preventive Services Task Force recommended annual lung cancer screening with low-dose computed tomography (LDCT) for high-risk patients in December 2013. We compared lung cancer screening-related opinions and practices among attending and resident primary care physicians (PCPs). Methods: In 2015, we conducted a 23-item survey among physicians at a large academic medical center. We surveyed 100 resident PCPs (30% response rate) and 86 attending PCPs (49% response rate) in Family Medicine and Internal Medicine. The questions focused on physicians’ opinions, knowledge of recommendations, self-reported practice patterns, and barriers to lung cancer screening. In 2015 and 2016, we compared responses among attending versus resident PCPs using chi-square/Fisher’s exact tests and 2-samples t-tests. Results: Compared with resident PCPs, attending PCPs were older (mean age =47 vs 30 years) and more likely to be male (54% vs 37%). Over half of both groups concurred that inconsistent recommendations make deciding whether or not to screen difficult. A substantial proportion in both groups indicated that they were undecided about the benefit of lung cancer screening for patients (43% attending PCPs and 55% resident PCPs). The majority of attending and resident PCPs agreed that barriers to screening included limited time during patient visits (62% and 78%, respectively), cost to patients (74% and 83%, respectively), potential for complications (53% and 70%, respectively), and a high false-positive rate (67% and 73%, respectively). Conclusion: There was no evidence to suggest that attending and resident PCPs had differing opinions about lung cancer screening. For population-based implementation of lung cancer screening, physicians and trainees will need resources and time to address the benefits and harms with their patients. Keywords: lung neoplasms, mass screening, physician behavior, surveys, questionnaires, low dose computed tomography, benefits, harms